Analisis semiologi Kaos Bonek Persebaya - Rini Damayanti; Agung Pranoto (Universitas Ahmad Dahlan, 2019)
The purpose of this study to determine the meanings of the writings on bonek t-shirts. There are characteristics and differences that occur when viewing the game Persebaya. The uniqueness is striking on the writings on the bonek t-shirts. With words that are meaningful and a love for Persebaya. The data source comes from some bonek shirts. This research uses Roland Barthes semiology theory. This study obtained data on the writings on t-shirts and banners during the Persebaya match, which is dominant from the writings that is to burn the spirit of the players and keep the big name of the team.